Mendeteksi Plagiarism Pada Dokumen Proposal Skripsi Menggunakan Algoritma Jaro Winkler Distance - Christina, Sherly; Oktaviyani, Enny Dwi; Famungkas, Buyung (STMIK Palangkaraya, 2018)
The practice of plagiarism among students in working on their thesis might happen. Plagiarism is done considering to the limited workmanship and lack of motivation to try with their own ability. It is necessary to provide a tool to prevent the act of plagiarism among the students. In this research, we built an application to detect the plagiarism on the thesis proposal. The application applies the Jaro Winkler Distance algorithm to detect the similarity from several documents. The first phase to detect the similarity of the thesis proposals is The text preprocessing phase of the document such as case folding, tokenizing, stopwords removal and stemming. Precision and Recall formula will be used to analyze the performance of the method in application. The test result of the data set shows the application could find the 80% relevant data that indicated the similarity. It means the application could contribute to detect the plagiarism on the thesis proposal document.